2018
DOI: 10.12659/ajcr.908465
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Cerebral Edema During Correction of Hyperglycemic Crises

Abstract: Patient: Male, 31Final Diagnosis: Mixed diabetic ketoacidosis and hyperglycemic hyperosmolar stateSymptoms: Acute encephalopathy and motor polyneuropathyMedication: Normal saline boluses followed by half-normal saline infusion • insulin dripClinical Procedure: —Specialty: Critical Care • Endocrine • Nephrology • NeurologyObjective:Unusual or unexpected effect of treatmentBackground:Hyperglycemic crises can cause severe neurologic impairment. One of the most dreaded consequences of hyperglycemic crises is cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…Hyperosmolarity was common among untreated dogs with non-ketonuric or ketonuric diabetes or the hyperosmolar hyperglycemic syndrome in several studies [6, 15]. Hyperosmolality is important to understand because it is associated with risk for osmotic complications in diabetic patients, including severe neurologic dysfunction, which may be fatal [23, 24, 25]. The frequency and range of osmotic complications due to hyperosmolality and, more specifically, hypertonicity in dogs are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperosmolarity was common among untreated dogs with non-ketonuric or ketonuric diabetes or the hyperosmolar hyperglycemic syndrome in several studies [6, 15]. Hyperosmolality is important to understand because it is associated with risk for osmotic complications in diabetic patients, including severe neurologic dysfunction, which may be fatal [23, 24, 25]. The frequency and range of osmotic complications due to hyperosmolality and, more specifically, hypertonicity in dogs are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Brain edema is more common in patients with Type 1 DM, but also can be seen in patients with type 2 DM. 5,32,33 However, in a study on children with Type 1 DM, it was observed that no ONSD alterations occurred in association with disease severity. 3 Similarly, in our study, it was determined that the ONSD measurements in the DKA and HHS patients were not different compared to those in the patients with isolated hyperglycemia.…”
Section: Discussionmentioning
confidence: 96%
“…Cerebral edema develops when fluid moves from the extracellular to the intracellular compartment faster than the brain cells can adapt to increased intracellular volume [ 8 ]. This can happen when there is rapid correction of hyperglycemia, leading to a sudden drop in serum osmolality.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism involves idiogenic osmoles, which are osmotically active substances produced within brain cells during periods of extracellular hyperosmolality to counteract the osmolar imbalance. These idiogenic osmoles have a slow clearance rate, resulting in high intracellular osmoles which can lead to the movement of extracellular fluid into the intracellular space [ 8 ].…”
Section: Discussionmentioning
confidence: 99%